SHI irradiation induced effects in functionalized MWCNTs - Saikiran, V.; Pathak, A. P.; Rao, N. Srinivasa; Devaraju, G.; Debgupta, Joyashish; Kyriakou, I.; Emfietzoglou, D. (Radiation Effects and Defects in Solids, 2012)
Multi-walled carbon nanotubes (MWCNTs) have attracted extensive attention globally due to their applications in modern nanotechnology. It is very important to study the effects on these MWCNTs under swift heavy ion (SHI) irradiation since ion irradiation has been recognized as one of the best tools for nanostructuring of materials, in general. Here, we present the effects of 80MeV Ni ions with a fluence ranging from 3 x 10(12) to 3 x 10(13) ions/cm(2) on functionalized MWCNT mats. The properties of pristine and irradiated samples were studied using X-ray diffraction, Raman spectroscopy and transmission electron microscopy. The effects of SHI irradiation on these samples are discussed in detail.
Keywords: CNT; Raman; SHI; TEM

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide